A new species of antipatharian coral (Cnidaria: Anthozoa: Antipatharia) from the southern California Bight. - Opresko, D. M. (Zootaxa, 2005)
A new species of antipatharian coral (Anthozoa: Antipatharia) is described from the southern California Bight. The species, Antipathes dendrochristos new species, forms large, multi-branched, bushy colonies that can reach a height of 2 m or more. The species is characterized by having small branchlets arranged primarily bilaterally and alternately, but in varying degrees of regularity; by small conical spines less than 0.1 mm tall, and by small polyps usually less than 1.4 mm in transverse diameter. The species occurs in colors of white, orange/gold, pinkish-orange, pink, red, and red-brown.